Digital Marketing Transformation in SMEs: Its Impact on Competitive Advantage - Desma Erica Maryati Manik; Sri Rezeki; Elisabeth Nainggolan; Susan Nainggolan (Dinasti International Journal of Education Management and Social Science, 2026)
This study aims to examine the impact of digital marketing transformation on the competitive advantage of small and medium-sized enterprises, with digital capability and customer engagement as supporting constructs, with marketing managerial competence as a mediating variable and digital marketing capability as a moderating variable. A quantitative approach with an explanatory research design was employed. Data were collected from MSME owners and managers using a structured questionnaire and analyzed using SEM-PLS. The findings reveal that market orientation and product differentiation have a positive and significant effect on marketing managerial competence, while marketing innovation does not show a significant effect. Product differentiation is identified as the most dominant factor influencing managerial competence. Furthermore, marketing managerial competence and digital marketing capability significantly enhance MSME marketing performance. In terms of indirect effects, marketing managerial competence mediates the relationship between product differentiation and marketing performance but does not mediate the effects of market orientation and marketing innovation. The moderating role of digital marketing capability is not supported, indicating that it functions primarily as a direct determinant of performance. This study contributes to the integration of competitive strategy and resource-based perspectives in explaining MSME performance. The findings highlight the importance of strengthening managerial competence and product differentiation as key drivers of sustainable marketing performance in MSMEs.